Pelvic Ultrasound in Diagnosing and Evaluating the Efficacy of Gonadotropin-Releasing Hormone Agonist Therapy in Girls With Idiopathic Central Precocious Puberty - Hong-kui Yu; Hong-kui Yu; Xiao Liu; Jia-kun Chen; Shan Wang; Xian-yue Quan (Frontiers Media S.A., 2019)
Background and Objective: Idiopathic central precocious puberty (ICPP) is characterized by early pubertal changes, the acceleration of growth velocity, and rapid bone maturation that often results in reduced adult height. Gonadotrophin-releasing hormone agonist (GnRHa) is currently considered to be an effective therapeutic agent. At present, GnRH stimulation test is adopted as a gold standard for the diagnosis of ICPP and the efficacy evaluation of GnRHa therapy. However, it is difficult to operate in practice due to the cumbersome procedures and multiple blood samples required. This study was conducted to establish the value of pelvic ultrasound in diagnosing ICPP and evaluating the efficacy of GnRHa therapy.Materials and Methods: One hundred and twenty-two girls with ICPP (ICPP group) were enrolled in the study. Pelvic ultrasound and levels of luteinizing hormone (LH) and follicle-stimulating hormone (FSH) were examined before and after GnRHa therapy for 3 months. Eighty normal prepubertal girls were enrolled as the control group. The difference in pelvic ultrasound parameters between the ICPP group before GnRHa therapy and the control group was compared by independent-sample t-test, while paired t-test for ICPP group before and after GnRHa therapy. Receiver operating characteristic (ROC) curve was used to explore the optimal pelvic ultrasound parameters for diagnosing ICPP. Pearson correlation analysis was performed between the pelvic ultrasound parameters and serum sexual hormone level.Results: The pelvic ultrasound parameters (length of the uterine body, anteroposterior diameter of the uterine body, transverse diameter of the uterine body, volume of the uterine body, uterine body-cervix ratio, length of the ovary, transverse diameter of the ovary, anteroposterior diameter of the ovary, volume of the ovary, number of increased follicles and maximum diameter of the follicle) in the ICPP group before GnRHa therapy were significantly larger than those of the control group (P < 0.05). All the above pelvic ultrasound parameters in the ICPP group were significantly decreased after GnRHa therapy compared with those before treatment (P < 0.05). The volume of the uterine body had the largest area under the ROC curve in differentiating between patients with ICCP and the control group. Pelvic ultrasound parameters were significantly correlated with serum sexual hormone levels (P < 0.05).Conclusion: This study indicates pelvic ultrasound is a simple and reliable tool to diagnose ICPP and evaluates the efficacy of GnRHa therapy by dynamically observing the morphology of internal genitalia. The volume of uterine body was the best ultrasound parameter to distinguish patients with ICPP from normal girls.